2020
DOI: 10.1371/journal.pone.0244965
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for texture analysis of QUS parametric images in the characterization of breast lesions

Abstract: Purpose Accurate and timely diagnosis of breast carcinoma is very crucial because of its high incidence and high morbidity. Screening can improve overall prognosis by detecting the disease early. Biopsy remains as the gold standard for pathological confirmation of malignancy and tumour grading. The development of diagnostic imaging techniques as an alternative for the rapid and accurate characterization of breast masses is necessitated. Quantitative ultrasound (QUS) spectroscopy is a modality well suited for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 69 publications
3
28
0
1
Order By: Relevance
“…This can be attributed to the fact that a linear classification algorithm works best only for linearly separable data. Nonlinear classification algorithms in the SVM-RBF methodology outperformed the other two classification algorithms as has been demonstrated previously in various contexts [25,26,29].…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…This can be attributed to the fact that a linear classification algorithm works best only for linearly separable data. Nonlinear classification algorithms in the SVM-RBF methodology outperformed the other two classification algorithms as has been demonstrated previously in various contexts [25,26,29].…”
Section: Discussionsupporting
confidence: 58%
“…Margin analysis akin to that in this study has been demonstrated earlier to have sufficient discriminative power to differentiate responders from non-responders [30]. In addition, margin analysis has also been explored in the characterization of breast lesions [25,26]. Tumour responses to NAC are thought to be different between responders and non-responders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Тому, щоб отримати найбільш інформативні характеристики та високу якість діагностичних моделей, в усіх випадках було використано дані текстурного аналізу, який ми успішно застосували в роботах [3][4][5][6]. Для отримання вхідних даних, необхідних для класифікації зображення, було прийнято рішення використати текстурний аналіз [10][11][12]. Ми застосовували різні підходи для отримання ознак текстурного аналізу через використання матриці відтінків сірого зображення (GM), матриці суміжності відтінків сірого (GLCM) [13] та матриці довжин пробігу відтінків сірого (GLRLM) [14].…”
Section: матеріали і методиunclassified